Enhancing Writing Skills through Recursive Strategy among Engineering Students - Selvi, M.D.Thamarai; Selvi, M.D.Thamarai; Kumar, Ramesh (International Journal of Psychosocial Rehabilitation, 2020)
The predominant purpose of this find out is to increase English writing capabilities of Engineering Students. They should be aware of how to deal with performance and competence errors. Problem Statement: 1. They are committing a lot of blunders in their written communicative competence. When students are asked to write free writing on any given subject matter (Essay), they are committing mechanical and fossilization errors. They are unable to comprehend how to decrease the performance and competence errors. 2. When they write essays, paragraphs, they are no longer capable to joint sentences and frame sentences coherently. They must understand how to use transitional phrases to link the sentences. 3 Moreover, they are familiar with limited vocabulary. 4. They are not aware of language knowledge. Objective: 1.To strengthens vocabulary skill 2. To be aware of about competence and performance errorsHypothesis: To keep away from the above problems in writing, the recursive approach, self-correction and peer-correction strategy used. By the usage of these approaches, the amount of error level can be decreased. Structure: B. E & B. Tech students are informants for the research survey. Techniques: Self- Correction, Peer-Correction and Recursive strategy usedConclusion: By the usage of this method in writing, the error level decreases. Suggesting this approach for in addition studies.